(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Acute appendicitis is one of the most common surgical emergencies and requires prompt diagnosis to prevent complications such as perforation, abscess formation, and peritonitis. The Alvarado score is a well-established tool, while the Lintula score is a relatively newer scoring system. Comparative evaluation of these scores may help identify the more effective method for diagnosing acute appendicitis. Aim: To compare the diagnostic accuracy of the Lintula Score and Alvarado Score in the diagnosis of acute appendicitis. Materials and Methods: This prospective comparative study was conducted over a period of 15 months in the Department of General Surgery, Sree Mookambika Institute of Medical Sciences, Kulasekharam. A total of 60 patients presenting with clinical suspicion of acute appendicitis were included in the study. Detailed history, physical examination, laboratory investigations, and radiological assessment were performed. Both Lintula and Alvarado scores were calculated for each patient at admission. The final diagnosis was confirmed by histopathological examination of the resected appendix. Sensitivity, specificity, positive predictive value, negative predictive value, and overall diagnostic accuracy of both scoring systems were analyzed and compared. Results: Majority of patients belonged to the age group of 21–40 years, with a mean age of 32.8 ± 11.4 years. Males constituted 38 (63.3%) patients and females 22 (36.7%) patients. Histopathological examination confirmed acute appendicitis in 52 (86.7%) patients, while 8 (13.3%) patients had a normal appendix. Using a cut-off score of ≥7, the Alvarado score demonstrated a sensitivity of 88.5%, specificity of 62.5%, positive predictive value of 93.9%, negative predictive value of 45.5%, and overall diagnostic accuracy of 85.0%. The Lintula score demonstrated a sensitivity of 92.3%, specificity of 75.0%, positive predictive value of 96.0%, negative predictive value of 60.0%, and overall diagnostic accuracy of 90.0%. Negative appendectomy rates were lower among patients stratified using the Lintula score. Both scoring systems were significantly associated with histopathological confirmation of appendicitis (p<0.001). Conclusion: Both the Lintula and Alvarado scoring systems are useful clinical tools for the diagnosis of acute appendicitis. However, the Lintula score demonstrated superior sensitivity, specificity, and overall diagnostic accuracy compared to the Alvarado score.